Tumpang Tindih Kewenangan dalam Penyelesaian Sengketa Perbankan Syariah - Jalil, Abdul (Jurnal Konstitusi, 2013)
This paper is going to discuss the decision of the Constitutional Court No. 93/ PUU-X/2012 related to granting of the petition for judicial review of Law No. 21 Year 2008 concerning Islamic Banking (State Gazette of the Republic of Indonesia Year  2008  Number  94,  namely  Article  55  paragraph  (2)  and  paragraph (3) governing the settlement of disputes with respect to Article 28D paragraph (1) of the 1945 Constitution, which says that the Act  should guarantee  legal  certainty and justice and do not have binding legal force. While in Article 55 paragraph (1), described Sharia Banking Dispute resolution by the court within the Religious Courts, while paragraph (2), stated in terms of the parties’ dispute has betoken  than those referred to in paragraph (1), the settlement of disputes in accordance with the contents of the Agreement, then, in paragraph (3) Settlement of disputes referred to in paragraph (2) must not conflict with Sharia. In addition to this, the paper will also question the extent of absolute authority of the Religious Courts institutions related to the settlement of economic disputes shari’a as stipulated in Law No. 3 of 2006 on Religious Courts    .